A prospective, multi-centre trial of PSMA-PET compared to FDG-PET for staging of newly diagnosed high risk prostate cancer - Matthew J. Roberts; Natasha A. Roberts; Anita Pelecanos; John W. Yaxley; Simon J. D. Harley; Amila R. Siriwardana; Karla Cullen; Marita Prior; Karen Lindsay; Ian Vela; Anna Kuchel; Nattakorn Dhiantravan; et al. (EJNMMI Research)
Abstract Background Despite being a potentially attractive alternative molecular imaging modality due to wider availability and association with lethal disease in advanced prostate cancer, the role of fluorodeoxyglucose (FDG)- positron emission tomography (PET) at initial diagnosis compared to Prostate Specific Membrane Antigen (PSMA) PET is yet to be accurately determined. The aim of this study was to evaluate the additive benefit of FDG PET to PSMA PET in patients with newly diagnosed, high risk prostate cancer. Results A prospective trial conducted across three sites between October-2021 and January-2023 recruited 32 participants with high risk (EAU classification) prostate cancer staged with PSMA PET-CT. FDG PET-CT was acquired centrally and reported with a standardised template. Median age was 69 years, median PSA was 14 ug/L, and most had PI-RADS 5 scores (59%) and ISUP Grade Group 5 tumours (66%). Overall, FDG-PET did not detect any additional definite/probable metastasis according to physician interpretation. All tumours showed PSMA avidity and higher stage was observed per PSMA-PET in 5 participants. No FDG uptake at the primary tumour occurred in 34% of participants. FDG-PET did not result in a change in management for any participant. PSA remission rates were lower in patients with stage ≥ 3 tumours on MRI (60% vs 94%, p = 0.04). Patient reported outcomes (PROs) were largely stable throughout the study. Conclusions FDG-PET did not provide additive staging information above PSMA-PET or alter management for newly diagnosed high-risk prostate cancer patients. Trial registration number : ANZCTR ACTRN12621001185853. Registered 03–09-2021. Available at https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=382299